Jellyfish, Lions, and Ducks: Sideways Spirals of Growth in Lucy Ellmann's Ducks, Newburyport. Issue 3 (October 2021) - Malewski, Anne; Lavery, Nick
Abstract : Focusing on the felt experience of consciousness, Lucy Ellmann's novel for adults Ducks, Newburyport (2019) undermines clear distinctions between the human protagonist's child and adult selves. Alongside references to non-human animals by this human narrator, entire sections present a mountain lioness's perspective. This essay places the concept of growing sideways from queer studies and children's literature scholarship into dialogue with cognitive literary studies to examine the human protagonist's spiralling between child/adult and human/non-human.